(untitled) (London Journal of Engineering Research, 2024)
Piping is one of the important causes of accidents in water conservancy facilities such as embankments and dams. Therefore, it is of great practical significance to study the timely plugging after the occurrence of dike piping. Based on the plugging of pipeline magnetic materials, this paper proposes a new method of plugging piping holes with PMC. Combined with the experimental method, the effects of different ratios of oily and waterborne polyurethane and the amount of magnetic powder on the plugging effect of PMC were investigated. The main results are as follow:(1) Under the same ratio of oily polyurethane and waterborne polyurethane, the more the magnetic content in the mixture, the easier the PMC is adsorbed by the strong magnetic field at the water inflow, and the more the magnetic material and polyurethane capsule are gathered in the water inflow. The comprehensive analysis shows that the magnetic capsule has the best plugging effect on piping when the content of magnetic material is 45g and 60g.(2) In the case of the same amount of magnetic materials, the ratio of oil polyurethane and waterborne polyurethane used in the test is 1:1,1:2,1:3,2:3, respectively. The water inflow curve is basically the same, and the more the proportion of oil polyurethane in the mixed polyurethane grouting fluid, the faster the PMC reacts with water, the less the final water inflow, and the four mixed polyurethane slurry ratios selected in the test can achieve better plugging effect. The research in this paper provides a good theoretical and experimental basis for piping rescue technology and magnetic material plugging in the future.